Nonobstructive gastroduodenal intussusception characterized by severe anemia: a case report - Benlei Zhu; Congming Wang; Jingwei Fu (Journal of International Medical Research)
Gastroduodenal intussusception is a relatively rare condition in adults and is typically caused by mobile pedunculated submucosal tumors arising from the stomach. Its clinical presentation often includes nonspecific signs of gastric outlet obstruction, such as nausea, vomiting, abdominal pain, epigastric fullness, or abdominal distention. We report a case of gastroduodenal intussusception in a 38-year-old woman who presented with severe anemia but no symptoms of gastric outlet obstruction. The preoperative diagnosis was established through esophagogastroduodenoscopy and computed tomography of the abdomen, and it was confirmed during surgery. Postoperative pathology and immunohistochemistry identified the tumor as a gastric leiomyoma.